Euripides in Albion: English translations and adaptations of dramatic Merope in the eighteenth and nineteenth centuries - Τσιχριτζή, Γεωργία (Πανεπιστήμιο Πελοποννήσου, 2022)
This dissertation concerns the European literary and theatrical reworkings of Euripides’ tragedy Cresphontes, and mainly the English translations and adaptations during the 18th and 19th centuries. The emphasis of the thesis on later works is due to the fact that Euripides' work has been virtually lost, except for a few fragments. Therefore, the thesis does not focus on Cresphontes, the main character of Euripides’ lost work, but on his wife Merope, one of the characters reworked by European dramatists. Cresphontes was the first king of Messenia, after the Descent of the Dorians, who was murdered by the usurper of the throne Polyphontes, along with two of his three children. The third one was secured by Merope until he came of age and returned to avenge his father's death and recapture the paternal throne. The story of Merope, known to ancient writers, became very popular on the European stage. During the late Renaissance, it was adapted by three well-known Italian writers of the 16th century and reworked by several distinguished French playwrights of the 17th century. Its climax, however, was reached during the 18th century, through three more adaptations (two Italian and one French) by Maffei (1714), Alfieri (1783) and Voltaire (1744) respectively. Thanks to the story and the reputation of these three authors, there soon appeared several English translations and adaptations of their works. Some works are faithful translations, while others are adaptations intended for the stage. The translations and adaptations were made by the following prominent literary personalities of the time: William Ayre (one of Alexander Pope’s biographers) who translated Maffei's work in 1740, Aaron Hill (advisor to Samuel Richardson) who adapted Voltaire's work in 1749, and Charles Lloyd (William Wordsworth’s friend) who translated Alfieri's work in 1815. The English translations and adaptations have experienced several reissues, while to this day they have remained little known. The thesis therefore tries to correct this deficiency by bringing together and discussing the English literary transformations of Merope’s story. The thesis has three main objectives. The first is to shed light on the historical and cultural background of the works’ creation and the reasons for their writing. The second is to offer new information about the identity of English writers, who are absent from Greek bibliography. The third is to identify the specific characteristics of the works, through their comparison with their Italian and French models, which gives them their own literary independence.
Ο Ευριπίδης στην Αλβιώνα: Αγγλικές μεταφράσεις και διασκευές της δραματικής Μερόπης κατά τον 18ο και 19ο αιώνα
Keywords: Ευριπίδης , 480-406 π.Χ. -- Ερμηνεία και κριτική; Ευριπίδης , 480-406 π.Χ. – Διασκευές; Ευριπίδης , 480-406 π.Χ. – Διασκευές -- Ιστορία και κριτική; Ευριπίδης , 480-406 π.Χ. – Μεταφράσεις, Αγγλικές; Ευριπίδης , 480-406 π.Χ. -- Κρεσφόντης; Ευριπίδης , 480-406 π.Χ. -- Εκτίμηση -- Αγγλία; Μερόπη, σύζυγος του Κρεσφόντη -- Δράμα; Euripides reception; Merope; European theatre; English translations and adaptations; Ευριπίδης πρόσληψη; Μερόπη; Ευρωπαϊκό θέατρο; Αγγλικές μεταφράσεις και διασκευές